Análise da implantação de valas de detenção na Avenida Segismundo Pereira, bacia do córrego Jataí, na cidade de Uberlândia/MG - Lima, Moisés Keniel Guilherme de (2017)
The presente paperwork propose the aplication of a green infrastructure, ditch of detention , in Segismundo Pereira, in the city of Uberlândia, Minas Gerais. At first, made a bibliographic review about Hidrologics’s theme, Urbanism Planning and studies of cases. Through of cases’s studies and current articles, it was possible to notice that green’s infrastructures has a lot of services at the cities, as infrastructures, laser, paisagism, well being and health. This paperwork shows model rainfall quantification of projects and applied equations to Uberlândia city as well. By means of modeling , using free softwares, as HEC-HMS (Hydrologic Engineering Center), got hydrograms with and without ditch of detention aplications. Was made a comparative of aplication’s influence of urban drainage on propose area. The results showed reduction on flow rate top of studied area.